2008
DOI: 10.3126/jer.v1i0.7953
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Development through Reflective Practice

Abstract: How can teachers learn to understand themselves? Who and what can help them in this process? This paper attempts to establish that reflection is a key for teachers to explore not only their selves but also that of the others. When teachers carry out systematic enquiry into themselves, they will understand themselves, their practices and their learners. By constantly looking into their own actions and experiences, they can professionally grow in their own work places. ! is paper discusses the process of reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
7
0
1
Order By: Relevance
“…Therefore, it has been extensively used in the West and developed world by educators, medical and nursing professionals, managers and other professionals for their own professional growth (Chivers, 2003;Clouder, 2000;Gnawali, 2008;Greenall, 2004;.…”
Section: Reflective Practice As Means To Develop Professionalsmentioning
confidence: 99%
“…Therefore, it has been extensively used in the West and developed world by educators, medical and nursing professionals, managers and other professionals for their own professional growth (Chivers, 2003;Clouder, 2000;Gnawali, 2008;Greenall, 2004;.…”
Section: Reflective Practice As Means To Develop Professionalsmentioning
confidence: 99%
“…Joshi et al's (2018) study on Nepalese EFL teachers' experience of professional development strategies reported that the EFL teachers benefited primarily from their own teaching experiences, self-monitoring workshops, and peer support. Similarly, Gnawali (2008), in his study what teacher development is and who is responsible for teacher professional development, resulted in teacher development as an ongoing process through which teachers keep growing with their voluntary effort (Head & Taylor, 1997). Djatmiko's (2011) study on the professional development of vocational teachers led to the introduction of vocational teachers in the development of selfdirected professions.…”
Section: Teacher Professional Development In Nepalmentioning
confidence: 99%
“…Preventing a view of education that is ritualized and embedded in unconscious behaviours, reflective practice offers a way of making sense of and revising actions that are a part everyday work as an educator. 23 In essence, this type of reflection on experience allows educators to make connections between tacit and explicit knowledge in a quest to gain insight into actions, recognize purpose, and generate a greater awareness of the impact educators have within the learning environment. This brings teacher education past the notion of training onto an educational path that makes assessments through continued attention to an examination of actions taken within educational settings.…”
Section: Reframing Experiences Through Revised Actionmentioning
confidence: 99%